The SIX1/LDHA Axis Promotes Lactate Accumulation and Leads to NK Cell Dysfunction in Pancreatic Cancer - Wanli Ge; Lingdong Meng; Shouji Cao; Chaoqun Hou; Xiaole Zhu; Dongya Huang; Qiang Li; Yunpeng Peng; Kuirong Jiang (Journal of Immunology Research)
Background. Pancreatic cancer (PC) is a malignant cancer with poor prognosis and high mortality rate. Sine oculis homeobox homolog 1 (SIX1) participates in the development of many cancers. However, the function of SIX1 in PC is not fully understood. Methods. SIX1 expression was determined using immunohistochemistry in PC tissues and cell lines. Glucose consumption, lactate production, and ATP assays were used to detect the function of SIX1. PC cells and NK cells were cocultured to study the effect of SIX1 overexpression in PC cells on NK cell function. Chromatin immunoprecipitation (ChIP) assays were used to study the relationship between SIX1 and lactate dehydrogenase A (LDHA). A series of in vitro and in vivo assays were further applied to elucidate the important role of the SIX1/LDHA axis in metabolism and NK cell dysfunction in PC. Results. SIX1 was significantly upregulated in PC tissue; SIX1 overexpression promoted the glycolysis capacity of PANC-1 and CFPAC-1 cells and resulted in NK cell dysfunction after the NK cells had been cultured with PC cells. LDHA inhibitor partially restored the promotion of PC caused by SIX1 overexpression. According to ChIP assays, SIX1 directly binds to the LDHA promoter region. Moreover, LDHA inhibitor and lactate transporter blocker treatment promoted the function of NK cells cocultured with PC cells. In vivo experiments yielded the same results. Conclusion. The SIX1/LDHA axis promotes lactate accumulation and leads to NK cell dysfunction in PC.